(untitled) (Annals of Medical Research, 2021)
Aim: Neurologic complication is the most complication of HIV infection, peripheral neuropathy, specifically with about 30-67% of HIV patients experiencing this condition. Distal sensory peripheral neuropathies (DSP) associated with severe pain and lack of a patient’s quality of life, and it has been documented to have up to 60% in advanced HIV prevalence. Other factors such as older ages, alcohol use, anti-tuberculosis drugs, low cell count of CD4+, deficiency of some nutrition, women, and high plasma viral load are announced as risk factors for PN in early publication.To perform a systematic review to identify risk factors estimates of peripheral neuropathy among HIV-infected adult patients.Material and Methods: We use the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement and checklist in this review. A search to review articles was performed in PubMed, MEDLINE, PROQUEST, EMBASE, and Google Scholar that were published from January 2014 to December 2018. We approved the latest five years of publications. Study titles were first screened, then second selection by title and abstract reviews. For the third and last selection, we tested those full text, then applied eligibility criteria.Results: We found 17795 citations, and at the end, four publications included. We found that age is a high-risk factor for peripheral neuropathy in HIV-patients, perhaps due to the increased risk of polyneuropathy as a consequence of oxidative stress and less efficient peripheral nerve regeneration among older people. Female was more likely to develop PN, although only one study confirmed this according to our analysis. Besides, PN was found higher among individuals who had previous CART use but later discontinued, thereby increasing the risk of PN. Of note, individuals with detectable viral load at entry had more probability of new DSP.Conclusion: Age, female sex, CART discontinuation, and initially, detectable viral load were at an increased risk of suffering from peripheral neuropathy in HIV-patients.